KONTRAK KARYA PERTAMBANGAN PT. FREEPORT DENGAN PEMERINTAH INDONESIA - Edho Chermando, Ery Agus Priyono, F.X. Joko Priyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Mining in Indonesia are increasingly mushrooming in Indonesia as a country that has the natural resources abundant to well-known in foreign countries, so many foreign businessmen interested to invest in Indonesia is therefore a form of cooperation is on offer by employers This stranger is a contract where it is the work of the foreign investor and the government of Indonesia. When in a contract need to consider several principles, namely principles of balance, the principle of freedom of contract and the principle of proportionality in terms of rights and obligations of each party, As well as checking menegenai terkadung several articles in the work contract of Civil Code section 1320. The second issue is the breach of contract committed by one party that does not menajalankan obligations under the contract the work. The method used by the authors in this research is the normative juridical method in which the author was just doing research about the contents of the contract or peel some of the provisions contained in the contract work. And compare with some of the theory to current contract. From the results of research on contract work of PT. Freeport Indonesia with the Indonesia government finally authors found that the contract by PT. Freeport Indonesia has embraced the principle of freedom of contract in the know of the contents of the contract is made by those who wish to perform the contract only and does not violate the current u, the principle of balance as well as both sides want each party to meet and implement the agreements and the principle of proportionality regarding the distribution of rights acquired by each party is in conformity with the letter contract and each chapter is in accordance with Article 1320 Civil Code. Regarding the breach of contract also stipulated in the contract work is about abitrase. Ie one that has been agreed by the respective parties to a treaty, ie the investor and the government of Indonesia.